The relationship among trade openness, foreign direct investment (FDI), Gross Domestic Investment (GDI) and economic growth in Thailand: 1970-2008 - Nuh, Ruslee (International Islamic University Malaysia, IIUM, 2011)
This study investigates the relationship among trade openness, foreign direct investment (FDI), gross domestic investment (GDI), and economic growth in Thailand from 1970-2008. The methodology is based on Johansen technique of Co-integration, Granger causality test based on VECM, and variance decomposition analysis. The cointegration analysis suggests that the variables are cointegrated and there exists a unique long-run relationship among the variables. The results of Granger causality test show that trade openness, foreign direct investment and gross domestic investment Granger caused economic growth unidirectionally except trade openness. The results of variance decomposition analysis indicate that foreign direct investment seems to be the most determinant of Thailand's GDP per capita growth, followed by trade openness and gross domestic investment. The study is very vital, especially to policy makers because it enables them to initiate, develop and manage long term economic strategies to achieve high economic growth.